Something happened: storytelling in a violent field - Harris, Bronwyn (International journal of transitional justice, 2018)
In 2014, something happened. Our colleague, AIDS activist and advocate of restorative justice, Harry Nyathela, was murdered. In the struggle to make sense of his senseless-seeming death, we reflect on the method of telling and listening to stories of violence in a ‘field’ that cannot be separated from everyday living (or dying). For researchers, there is little guidance on how to engage when something violent or traumatic happens. Suffering can never be brought fully into language; it is experiential and there is always a risk that we ‘steal the pain’ of others while trying to articulate it. Yet, because stories have the potential to affect those who tell and listen to them, narrative methods may enable recognition and establish a basis for transformative meaning making. We remember Harry Nyathela in this Note from the Field and invite methodological conversation about research in contexts where affecting, haunting things happen.